Handbook of waterfront cities and urbanism - Rahman, M. Mahbubur (Routledge, 2023)
"Handbook of Waterfront Cities and Urbanism is the first resource to address cities' transformations of their coastlines and riverbanks and the resulting effects on environment, culture, and identity in a genuinely global context. Spanning cities from Gdańsk to Georgetown, this reference for design, development, and planning explores the transition of waterfronts from industrial and port zones to crowd-drawing urban spectacles within the frameworks of urban development, economics, ecology, governance, globalization, preservation, and sustainability. A collection of contextual studies, local perspectives, project reviews, and analyses of evolution and emerging trends provides critical insight into the phenomenon of waterfront development and urbanism in cities from the East to the West. Features: Explores the transformation of waterfronts from industrial hubs to urban playgrounds through the lenses of preservation, governance, economics, ecology, and more. Presents chapter-length case studies drawn from cities in China, Bangladesh, Turkey, the United States, Malaysia, the European Union, Egypt, and other countries. Includes contributions from an interdisciplinary team of international scholars and professionals, a much-needed corrective to the historical exclusion of researchers and issues from the Global South. An ideal reference for graduate students, scholars, and professionals in urban planning, architecture, geography, and history, the Handbook of Waterfront Cities and Urbanism deserves to be on the shelf of urban authorities and any internationally-minded academic or practitioner in real estate development, water management, preservation, or tourism"--